EVALUASI PERFORMA ALGORITMA HILL CIPHER DAN AFFINE CIPHER PADA PENGAMANAN DATA PENGGUNA WEBSITE E-COMMERCE : PERFORMANCE EVALUATION OF HILL CIPHER AND AFFINE CIPHER ALGORITHMS IN SECURING E-COMMERCE WEBSITE USER DATA - Ona Mazura; Nurmi Hidayasari (LPPM Universitas Abdurrab, 2026)
User data security is a crucial aspect in e-commerce systems, especially to protect sensitive data stored in databases (data at rest). One approach that can be used to maintain the confidentiality of this data is the application of cryptographic algorithms. This study aims to evaluate the performance of the classic cryptographic algorithms Hill Cipher and Affine Cipher in securing user data on web-based e-commerce websites. The research method is carried out by implementing both algorithms in an e-commerce system and conducting tests on the encryption and decryption processes of user data. The evaluation focused on two main aspects, namely the efficiency of the processing time and the quality of the resulting ciphertext. Security testing was carried out using the Ciphertext Only Attack approach and measuring the level of ciphertext randomness using Shannon Entropy. The test results show that the Affine Cipher algorithm has a faster encryption and decryption processing time than the Hill Cipher, making it more efficient in terms of performance. Conversely, the Hill Cipher produces ciphertext with a slightly higher level of randomness, as indicated by a larger Shannon Entropy value. This finding indicates a trade-off between processing speed and the quality of ciphertext randomness in both classic cryptographic algorithms. This research contributes by conducting a head-to-head comparative evaluation between Hill Cipher and Affine Cipher in the context of securing stored data in web-based e-commerce systems. The results are expected to be used as considerations in selecting classical cryptographic algorithms for learning, simulation, or small-scale systems with limited computational requirements.